2014
DOI: 10.1002/ece3.986
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the role of the close‐range effect and environmental variables in the occurrence and spread of Phragmites australis in four sites on the Finnish coast of the Gulf of Finland and the Archipelago Sea

Abstract: Phragmites australis, a native helophyte in coastal areas of the Baltic Sea, has significantly spread on the Finnish coast in the last decades raising ecological questions and social interest and concern due to the important role it plays in the ecosystem dynamics of shallow coastal areas. Despite its important implications on the planning and management of the area, predictive modeling of Phragmites distribution is not well studied. We examined the prevalence and progression of Phragmites in four sites along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 79 publications
(208 reference statements)
0
11
0
Order By: Relevance
“…The latter is the case in our model; we used boosted regression trees (BRT) ea ML techniquee to provide the transition probabilities based on the habitat suitability and the neighborhood conditions. BRT have been applied in a number of SDM studies and for Phragmites modeling in particular (Altartouri et al, 2014), and have been found to outperform other ML methods (Caruana and Niculescu-Mizil, 2006;Elith et al, 2006). The BRT method is rooted in both statistics and ML (Elith et al, 2008).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The latter is the case in our model; we used boosted regression trees (BRT) ea ML techniquee to provide the transition probabilities based on the habitat suitability and the neighborhood conditions. BRT have been applied in a number of SDM studies and for Phragmites modeling in particular (Altartouri et al, 2014), and have been found to outperform other ML methods (Caruana and Niculescu-Mizil, 2006;Elith et al, 2006). The BRT method is rooted in both statistics and ML (Elith et al, 2008).…”
Section: Methodsmentioning
confidence: 97%
“…These variables are proxies to functional, resource, and disturbance factors, as explained in Section 1.1. They have been found to be good predictors of the occurrence of Phragmites in the Northern Baltic area in general and in Southern Finland in particular (von Numers, 2011;Meriste et al, 2012;Pitk€ anen et al, 2013;Altartouri et al, 2014).…”
Section: The Habitat Suitability Sub-modelmentioning
confidence: 96%
See 1 more Smart Citation
“…The overall aim of this study is to determine temporal and spatial spectral variability of reed beds in the Olkiluoto Island. More specifically, the objectives of this study are: (1) to characterize the spectral properties of the dominant wetland species Phragmites Australis in different phenological stages and to identify the most suitable time to discriminate it from other green vegetation; (2) to study the spatial variability of reed spectra and evaluate the effects of this variability on reed bed mapping; and (3) to suggest promising methods to be used in reed bed mapping.…”
Section: Study Areamentioning
confidence: 99%
“…Common reed (Phragmites Australis), a native helophyte in coastal areas of the Baltic Sea, has significantly spread on the Finnish coast during the last decades raising ecological issues and concerns due to the important role it plays in the ecosystem dynamics of shallow coastal areas [1]. In addition to biodiversity there are other ecological and economic issues such as water protection, bioenergy, construction, farming and landscape.…”
Section: Introductionmentioning
confidence: 99%